Higher ultraviolet skin reflectance signals submissiveness in the anemonefish, Amphiprion akindynos. (1st November 2022) - Mitchell, Laurie J; Cortesi, Fabio; Marshall, N Justin; Cheney, Karen L
Abstract: Ultraviolet (UV) vision is widespread among teleost fishes, of which many exhibit UV skin colors for communication. However, aside from its role in mate selection, few studies have examined the information UV signaling conveys in other socio-behavioral contexts. Anemonefishes (subfamily, Amphiprioninae) live in a fascinating dominance hierarchy, in which a large female and male dominate over non-breeding subordinates, and body size is the primary cue for dominance. The iconic orange and white bars of anemonefishes are highly UV-reflective, and their color vision is well tuned to perceive the chromatic contrast of skin, which we show here decreases in the amount of UV reflectance with increasing social rank. To test the function of their UV-skin signals, we compared the outcomes of staged contests over dominance between size-matched Barrier Reef anemonefish ( Amphiprion akindynos ) in aquarium chambers viewed under different UV-absorbing filters. Fish under UV-blocking filters were more likely to win contests, where fish under no-filter or neutral-density filter were more likely to submit. For contests between fish in no-filter and neutral density filter treatments, light treatment had no effect on contest outcome (win/lose). We also show that sub-adults were more aggressive toward smaller juveniles placed under a UV filter than a neutral density filter. Taken together, our results show that UV reflectance or UV contrast in anemonefish can modulate aggression and encode dominant and submissive cues, when changes in overall intensity are controlled for. Abstract : When signaling submission, it is important to wave the "white flag." In the Barrier Reef anemonefish, ultraviolet color patterns serve to signal submissiveness. In staged contests over dominance between size-matched anemonefish, low ultraviolet skin reflectance strongly predicted fish winning a contest, while high UV skin reflectance predicted losing. We demonstrate that juvenile subordinates benefit by signaling their submissiveness with a naturally higher ultraviolet skin reflectance which evokes less aggression from larger, more-dominant fish and likely aids with social group integration.